Penggunaan metode eksperimen untuk meningkatkan motivasi belajar IPA pada tema peristiwa dalam kehidupan bagi siswa kelas VA SD Negeri 2 Leteh kecamatan Rembang Kabupaten Rembang - S Zulaekho (Universitas Sebelas Maret, 2020)
Abstract. the purpose of this research is increasing the VA Class of 2 Leteh Elementary School, Sub district of Rembang, Regency of Rembang, students’ learning motivation by using experiment method in natural science, theme of phenomenon in life, of the second Semester of the 2017/2018 Year Academic. The type of this research is a class action research in two cycles. The subjects of this research are the VA Class students of 2 Leteh Elementary School, Sub district of Rembang, Regency of Rembang, as much as 46 students. Technique of collecting data of this research is questioner. Technique of analyzing data of this research is qualitative descriptive. The result of this research showed that using experiment method increase the VAClass of 2 Leteh Elementary School, Sub district of Rembang, Regency of Rembang students’ learning motivation in natural science, theme of phenomenon in life. On Early Condition, the average of learning motivation is 34,25% as low category. Then on the First Cycle, the average of learning motivation increase on 57,08% as middle category and on the Second Cycle, the average of learning motivation increase on 77,63% as high category. Kata kunci: experimental method, learning motivation, science, elementary school